A Flow-of-Funds Model of Portfolio Behaviour of Nigerian Commercial Banks. - Odedokun, Matthew Odeyinka (Obafemi Awolowo University, 2014)
Commercial banks use funds at their disposal to finance cash holding in various forms and investments in various securities and to grant various loans and advances. The study investigates the factors that determine the amount of funds used in each of the above ways. Commercial banks also sometimes consciously borrow in order to expand their asset holdings. The study also investigates their borrowing behaviour.